Economic Return from Thysanolaena maxima (Roxb) Kuntze (Broom Grass) Cultivation in Nian Village, Longleng, Nagaland, India - Chubakumzuk Jamir; Yanyak (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
Thysanolaena maxima (Roxb) Kuntze is a wild grass cultivated by the farmers of Nian village for the production of broom panicles, which has high demand in the market. In recent years T. maxima has emerged as an important agro based product transforming the rural economy. The objective of this research was aimed at investigating the effect of plant density on income of the farmers cultivating this broom grass. The data were collected in cooperation with farmers by using pre-tested interview schedule. Total of 50 respondents i.e., Thysanolaena maxima (Roxb) Kuntze (Broom grass) growers were selected using random sampling technique. The results revealed that the growth and production of broom panicles were significantly impacted by plant density. The production of panicles in the plantations with lower plant density was significantly higher than those grown in higher plant density. The study concludes that plantation rose at a density of 1500 plants ac-1gave highest net present value of ₹74124.04 ac-1year-1 up to three harvests. Based on the study, it is concluded that a density of 1500 plants/ac can be recommended for optimum economic return from cultivation of T. maxima.